Ah, sweet mystery of life: the country stories of roald dahl - Dahl, Roald (Penguin London, 1990)
Roald Dahl describes country life in his off-beat way. All the tales about rat-catching, maggot-breeding, poaching and the eccentricities of country life are dealt with in a sophisticated and witty way